2014
DOI: 10.3390/v6124914
|View full text |Cite
|
Sign up to set email alerts
|

In between: Gypsy in Drosophila melanogaster Reveals New Insights into Endogenous Retrovirus Evolution

Abstract: Retroviruses are RNA viruses that are able to synthesize a DNA copy of their genome and insert it into a chromosome of the host cell. Sequencing of different eukaryote genomes has revealed the presence of many such endogenous retroviral sequences. The mechanisms by which these retroviral sequences have colonized the genome are still unknown, and the endogenous retrovirus gypsy of Drosophila melanogaster is a powerful experimental model for deciphering this process in vivo. Gypsy is expressed in a layer of soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Finally, we tested whether the shortened lifespan of piRNA pathway mutants was dependent upon TE activity. Many TEs in Drosophila are retrotransposons, including gypsy , and depend upon reverse transcriptase for their replicative mobility32. Administration of a known reverse transcriptase inhibitor, 3TC, inhibits the normal age-related increase in gypsy mobilization and extends the shortened lifespan of Dcr-2 mutants, another condition in which derepression of TEs occurs9.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we tested whether the shortened lifespan of piRNA pathway mutants was dependent upon TE activity. Many TEs in Drosophila are retrotransposons, including gypsy , and depend upon reverse transcriptase for their replicative mobility32. Administration of a known reverse transcriptase inhibitor, 3TC, inhibits the normal age-related increase in gypsy mobilization and extends the shortened lifespan of Dcr-2 mutants, another condition in which derepression of TEs occurs9.…”
Section: Resultsmentioning
confidence: 99%
“…Another element in D. melanogaster, Grp, thought to be the gag gene of a gypsy element, is expressed in an age-and gender-specific manner in the insects and also may provide protection (127). The insect ERVs have provided a rich resource for understanding the endogenization process (128).…”
Section: Endogenous Retrovirusesmentioning
confidence: 99%
“…gypsy (Song et al, 1994;Teysset et al, 1998;Touret et al, 2014), emerged upregulated 101 in TBPH-minus heads compared to controls demonstrating by a different methodology 102 that the activity of this retrotransposon was increased in mutant tissues ( Figure 1C). More 103 importantly, we found that the genetic expression of the TBPH protein was able to 104 repress the activation of accord and gypsy in TBPH mutant backgrounds, demonstrating 105 that the role of TBPH was rather specific ( Figure 1B and C).…”
mentioning
confidence: 95%